The Effect of Cash Flow, ROA, Rupiah Exchange Rate, Company Size, NPM, DER on Stock Returns in Textile and Garment Sub-Sector Manufacturing Companies Listed on the IDX for the 2018-2020 Period - Bayu Wulandari; Varins L C BR Manullang; Dery Anggreni Tarigan Tua; Intan Sari Sitanggang (Budapest International Research and Critics University, 2021)
This study aims to test whether cash flow, return on assets, rupiah exchange rate, company size, net profit margin, and debt equity ratio have an effect on the company's stock return. This research was conducted on textile and garment sub-sector manufacturing companies for the period 2018 – 2020 with a research population of 21 (twenty one) companies listed on the Indonesia Stock Exchange. The sampling technique used in this research is purposive sampling and then obtained a sample of 10 (ten) companies. The data used are the financial reports of each sample company published on the www.idx.co.id website. The research method used is associative analysis method and multiple linear regression analysis method. The dependent variable is cash flow, return on assets, rupiah exchange rate, company size, net profit margin, and debt equity of ratio. The results showed that partially cash flow and return on assets had a significant effect on stock returns, while the rupiah exchange rate, company size, net profit margin, and debt equity of ratio had no significant effect on stock returns.